Women in European Academies : From Patronae Scientiarum to Path-Breakers - Barbara, Stollberg-Rilinger; Brigitte, Mazohl; Doris A., Corradini; Eberhard, Knobloch; Eleanor, Dodson; Eoin, Mac Cárthaigh; Ernst, Osterkamp; Eva, Haettner Aurelius; Frevert, Ute; Günter, Stock; Hanna, Krajewska; Jan, Kusber; et al. (2021)
The volume examines the lives and achievements of women who played determining roles in the history of European academies and in the development of modern science in Europe. These persevering personalities either had a key influence in the establishment of academies ("Patronae Scientiarum") or were pioneering scientists who made major contributions to the progress of science ("path-breakers"). In both cases, their stories provide unique testimonies on the scientific institutions of their time and the systemic barriers female scientists were facing. Conceptualized as a transversal series of biographical portraits, the contributions focus particularly on each personalities’ role in (or relation to) European academies, ensuring both a geographical and disciplinary balance. The co-editors of the volume are Professor Ute Frevert (Co-Director at the Max Planck Institute for Human Development), Professor Ernst Osterkamp (President of the Deutsche Akademie für Sprache und Dichtung) and Professor Günter Stock (former ALLEA President).